Empowerment of Posyandu Cadres in Improving the Welfare in Sangir Jujuan, South Solok Regency - Aizah Nurulnia; Reni Susanti; Beni Putra Hanafi (Indev: Literasi Media Dakwah dan Pengembangan Masyarakat, 2022)
The main problem in this thesis is the factors that support and hinder the efforts of posyandu cadres in improving the welfare of mothers and children in Jorong Sungai Galugu, Nagari Bidar Alam, Sangir Jujuan District, South Solok Regency. The purpose of this discussion is to find out what are the factors that influence posyandu cadres in the welfare of mothers and children in Jorong Sungai Galugu Nagari Bidar Alam. The type of research that the author uses is a type of field research (Field Research) with qualitative methods, to obtain data and the problems studied. The data collection technique that the author uses is through observation, interviews, and documentation, and the data sources used are primary and secondary data sources. The inhibiting factors for the efforts of posyandu cadres in Jorong Sungai Galugu are seen from the many posyandu targets who do not bring their children to the posyandu, and inadequate posyandu equipment. Then the obstacles faced by medical personnel at the posyandu were their midwives who could not attend, while the obstacles experienced by the posyandu targets were the factors of their work that could not be left behind, houses that were far from the posyandu implementation location, information that did not reach the posyandu targets, and the lack of cadre services.